Health Outcomes Associated with Self-Reported Vision Impairment in Older Adults. (November 2016) - Steinman, Bernard A.
Introduction: To compare the health status of older adults with and without vision impairment, this study employed a disability framework consisting of four stages, progressing from risk factors; through pathology and impairments that result in declining functioning; and eventually to disability. Methods: Data from five rounds (1999 to 2008) of the National Health and Nutrition Examination Study were analyzed. Binary and multinomial logistic regression were used to estimate odds ratios, with 95% confidence intervals reflecting the likelihood of negative health outcomes among persons with self-reported fair and poor vision relative to persons with good vision. Results: Fair and poor vision status were associated with negative health outcomes across the four health dimensions. Discussion: Disparities in health among vision status groups may originate as a result of limitations in daily activities that could lead to changes in diet, health maintenance, and activity levels. Alternatively, disparities may reflect primary pathologies and conditions that are secondarily related to poor vision status. Longitudinal research is suggested in order to assess the order of key events, and to make a more powerful assertion of causality. Implications for practitioners: Comparisons of health outcomes by vision status are important because of the potential to identify points in the disability framework where effective interventions could prevent progression to later stages in the disability process.